I just work here! Employees as co-creators of the employer brand - Näppä, Anna; Ek Styvén, Maria; Foster, Tim (Scandinavian Journal of Hospitality and Tourism, 2023)
This study explores the role of employees as both a target group and co-creators of employer brand equity in tourism and hospitality. Extant research has largely focused on the effects of external employer brands; however, studies on internal employer branding have been lacking. The research problem is addressed through the conceptual lens of employer brand equity. To provide empirical insights into employee experiences, exploratory in-depth interviews were conducted with 16 employees in hotels, restaurants, and retail stores in Northern Sweden. While employees constitute a target market for internal employer branding, they also co-create the employer value proposition. Employees act as brand members, representatives, advocates and influencers, increasing knowledge about the organization internally and externally. However, in practice, companies in the service sector seem to place more focus on the customer experience than on reminding the employees of the brand promise towards them. This study identifies and describes the role of employees in the employer branding process by developing a new conceptual framework. Thereby, it adds to the understanding of co-creation in employer branding, an under-researched area which has been suggested to become a new paradigm in the employer branding literature. Validerad;2023;Nivå 2;2023-06-30 (joosat); Funder: Handelsrådet (2016-211)